The common difference is 2
Answer:
(m? - 5 m +6 ) ÷ (m - 2) = ![\frac{m}{-5m+6} / (m - 2)](https://tex.z-dn.net/?f=%5Cfrac%7Bm%7D%7B-5m%2B6%7D%20%2F%20%28m%20-%202%29)
Step-by-step explanation:
Divide the first expression by the second expression.
![\frac{m}{-5m+6} / (m - 2)](https://tex.z-dn.net/?f=%5Cfrac%7Bm%7D%7B-5m%2B6%7D%20%2F%20%28m%20-%202%29)
I hope this helps.
Answer:
x + 4√(x + 2) + 6
Step-by-step explanation:
All we need to do is expand by using FOIL (First, Outside, Inside, Last):
x + 2 + 2√(x + 2) + 2√(x + 2) + 4
Then we combine like terms to get our final answer:
x + 2 + 4√(x + 2) + 4
x + 4√(x + 2) + 6
Answer:
don't know..I am not fully understand.
can u please bhut other example
Answer:
Lana is 15 and Susan is 30
Step-by-step explanation:
let Lana's age=x
Susan's age=2x
Their ages four years ago:
Lana=x-4
Susan=2x-4
Now their ages 4years ago was 37 so:
x-4+2x-4=37
3x-8=37
3x=37+8
3x=45
x=15
Since Lana's age is x,she is 15years
Since Susan's age is 2x,she is 30years